Unwanted incidents during transition of geriatric patients from hospital to home: a prospective observational study - Sletvold Olav; Helbostad Jorunn L; Mesteig Marianne; Røsstad Tove; Saltvedt Ingvild (BMC, 2010)
Abstract Background Geriatric patients recently discharged from hospital experience increased chance of unplanned readmissions and admission to nursing homes. Several studies have shown that medication-related discrepancies are common. Few studies report unwanted incidents by other factors than medications. In 2002 an ambulatory team (AT) was established within the Department of Geriatrics, St. Olavs University Hospital HF, Trondheim, Norway. The AT monitored the transition of the patients from hospital to home and four weeks after discharge in order to reveal unwanted incidents. The aim of the present study was to describe unwanted incidents registered by the AT among patients discharged from a geriatric evaluation and management unit (GEMU) by character, frequency and stage in the transitional process. Only unwanted incidents with a severity making contact with the primary health care (PHC) necessary were registered. Methods A prospective observational study with patients treated in the GEMU and followed by the AT was performed. Current practice included comprehensive geriatric assessment and management including discharge planning in the GEMU and collaboration with the primary health care on appointments on assistance to be provided after discharge from hospital. Unwanted incidents severe enough to induce contact with the primary health care were registered during the transitional phase and after discharge. Results 118 patients (65% female), with mean age 83.2 ± 6.4 years participated. Median Barthel Index at discharge was 18 (interquartile range 16-19) and median Mini Mental Status Examination 24 (interquartile range 21-26). A total of 146 unwanted incidents were registered in 70 (59%) of the patients. Most frequent were unwanted incidents related to drug prescription regime (32%), exchange of information in and between the GEMU and the primary health care (25%) and service or help provided from the PHC (17%). Conclusions Despite a seemingly well-organised system for transition of patients from the GEMU to their homes, one or more unwanted incidents occurred in most patients during discharge or four weeks post discharge. The study has revealed areas of importance for improving transitional care of geriatric patients.